PENYULUHAN PENERAPAN PROTOKOL KESEHATAN BAGI MASYARAKAT DESA KUMBUNG KECAMATAN RAJAGALUH - Syamsuddin Amin, Ali (JURNAL PARAHITA ABDIMAS: Jurnal Pengabdian Masyarakat, 2020)
The implementation of the community service program in Kumbung Village through outreach activities on the application of health protocols is motivated by the phenomenon of low public awareness in implementing health protocols as a result of low knowledge about the Covid-19 pandemic outbreak that has occurred since the beginning of 2020. Extension activities for implementing health protocols are one of the solutions. To solve problems faced by the community, its implementation is integrated with the Majalengka University Student Real Work program in 2020. Activity materials: a) Introduction to the Covid-19 pandemic and ways to overcome its spread; b) The importance of discipline and cooperation in implementing health protocols; c) Distribute free masks. The implementation has the full support of the Village government and very good community participation. As a result of this activity, there was an increase in public awareness and willingness to implement health protocols on their own awareness.